2015
DOI: 10.1371/journal.ppat.1004828
|View full text |Cite
|
Sign up to set email alerts
|

A Two-Component DNA-Prime/Protein-Boost Vaccination Strategy for Eliciting Long-Term, Protective T Cell Immunity against Trypanosoma cruzi

Abstract: In this study, we evaluated the long-term efficacy of a two-component subunit vaccine against Trypanosoma cruzi infection. C57BL/6 mice were immunized with TcG2/TcG4 vaccine delivered by a DNA-prime/Protein-boost (D/P) approach and challenged with T. cruzi at 120 or 180 days post-vaccination (dpv). We examined whether vaccine-primed T cell immunity was capable of rapid expansion and intercepting the infecting T. cruzi. Our data showed that D/P vaccine elicited CD4+ (30-38%) and CD8+ (22-42%) T cells maintained… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
41
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(42 citation statements)
references
References 59 publications
(88 reference statements)
1
41
0
Order By: Relevance
“…56,57 This is the first reported study utilizing a nanoparticle delivery system approach in developing a therapeutic vaccine against Chagas disease. Our findings of parasite reduction, but not elimination, are similar to the majority of Chagas disease vaccine studies.…”
Section: Discussionmentioning
confidence: 99%
“…56,57 This is the first reported study utilizing a nanoparticle delivery system approach in developing a therapeutic vaccine against Chagas disease. Our findings of parasite reduction, but not elimination, are similar to the majority of Chagas disease vaccine studies.…”
Section: Discussionmentioning
confidence: 99%
“…[76] In a recent study, it was demonstrated that TcG2 and TcG4 DNA prime/protein boost vaccine achieved long-term protection against T. cruzi infection and Chagas disease, suggesting the vaccine-induced effector T cells can be long-lived and provide protection from parasitic infection. This vaccine-induced immunity waned slightly after 6 months post booster immunization, but was still sufficient to provide twofold control of invading pathogens [77] that, according to mathematical modeling, is sufficient to break the parasite transmission cycle [78] and prevent disease progression. [79] Pertinent to the theme of this review, it is important to note that many of the studies discussed highlight the importance of a preventive or therapeutic vaccine to control T. cruzi infection by at least decreasing parasite burden, cardiac tissue inflammation and damage or increasing survival if not providing sterile immunity.…”
Section: Vaccine Developmentmentioning
confidence: 99%
“…T. cruzi (SylvioX10/4) and C2C12 cells (an immortalized, mouse-derived myoblast cell line) were purchased from American Type Culture Collection (ATCC, Manassas VA) and T. cruzi trypomastigotes (infective stage) were propagated in C2C12 cells . T. cruzi antigens TcG2 and TcG4 were used as vaccine candidates and have been described in detail previously [19, 20]. Mice (n = five per group per experiment, two experiments) were injected in the quadriceps muscle with TcG2 and TcG4 antigens that were delivered as DNA-prime/protein-boost vaccine [19, 20].…”
Section: Methodsmentioning
confidence: 99%
“…T. cruzi antigens TcG2 and TcG4 were used as vaccine candidates and have been described in detail previously [19, 20]. Mice (n = five per group per experiment, two experiments) were injected in the quadriceps muscle with TcG2 and TcG4 antigens that were delivered as DNA-prime/protein-boost vaccine [19, 20]. Two weeks after immunization, mice were challenged with T. cruzi trypomastigotes (10,000/mouse), and sacrificed at ~120 days post-infection (pi), corresponding to the chronic disease phase [19, 20].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation